2004
DOI: 10.1103/physrevlett.93.257201
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Induced Quantum Phase Transition in the Spin-LiquidTlCuCl3

Abstract: The condensation of magnetic quasiparticles into the nonmagnetic ground state has been used to explain novel magnetic ordering phenomena observed in quantum spin systems. We present neutron scattering results across the pressure-induced quantum phase transition and for the novel ordered phase of the magnetic insulator TlCuCl3, which are consistent with the theoretically predicted two degenerate gapless Goldstone modes, similar to the low-energy spin excitations in the field-induced case. These novel experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(51 citation statements)
references
References 30 publications
(49 reference statements)
1
50
0
Order By: Relevance
“…The magnetic excitation spectrum has again the nature of a gapless Goldstone mode (Matsumoto et al, 2004) which was experimentally confirmed in the pressure-induced ordered phase as shown in Fig. 57(b) (Rüegg et al, 2004a). In later INS experiments, it was demonstrated that only the longitudinal and one transverse triplet component soften at p c , whereas the other transverse triplet component retains a finite gap at p c .…”
Section: B Dimer-based Antiferromagnetsmentioning
confidence: 78%
“…The magnetic excitation spectrum has again the nature of a gapless Goldstone mode (Matsumoto et al, 2004) which was experimentally confirmed in the pressure-induced ordered phase as shown in Fig. 57(b) (Rüegg et al, 2004a). In later INS experiments, it was demonstrated that only the longitudinal and one transverse triplet component soften at p c , whereas the other transverse triplet component retains a finite gap at p c .…”
Section: B Dimer-based Antiferromagnetsmentioning
confidence: 78%
“…At the transition between these two very different forms of order, the ground-state wavefunction is entangled over macroscopic length scales. Recent neutron scattering experiments have revealed the emergence of new bosonic quasiparticles at magnetic quantum-critical points [26][27][28] . Ordinary magnets exhibit well-defined spin waves that modulate the direction of the magnetization, but the longitudinal modes that modulate its amplitude (roughly analogous to the Higgs modes found in superconductors and in particle physics 29 ) are usually found at much higher energies and are strongly mixed with multimagnon excitations.…”
Section: Quantum Collective Phenomenamentioning
confidence: 99%
“…Until recently only one good experimental realization of a pressure-induced QPT had been found, namely that in the three-dimensional dimer system TlCuCl 3 . [3][4][5] Further work has lead to fascinating insights, in particular to the observation of a massive amplitude mode, 6,7 the magnetic analog of the Higgs boson. 8 Quantum magnets built from organic molecules can be very susceptible to perturbation by external pressure due to their 'soft' molecular frameworks.…”
Section: Introductionmentioning
confidence: 99%